The Effect of Fatigue on Single-Leg Postural Sway and Its Transient Characteristics in Healthy Young Adults - Kozinc, Žiga; Trajković, Nebojša; Smajla, Darjan; Šarabon, Nejc (Frontiers in Physiology, 2021)
Neuromuscular fatigue is known to impair balance ability, which is reflected in increased postural sway during quiet standing tasks. Recently, quantifying transient characteristics of postural sway has been suggested as an approach to obtain additional information regarding postural control. However, this approach is currently vastly unexplored. The purpose of this study was to investigate the effects of fatigue (induced by a repeated change of direction task) on postural sway and its transient characteristics during single-leg standing, including whole-trial estimates and indexes of transient behavior in young healthy active adults. The study involved 28 physically active students (14 females). Single-leg postural sway was recorded for 30 s before and after a fatiguing protocol, which consisted of a repeated change of direction tasks. We calculated the traditional whole-trial estimates of postural sway (center-of-pressure (CoP) velocity and amplitude in anterior-posterior (AP) and medial-lateral (ML) directionsand corresponding transient behavior indexes, based on three 10-s intervals. Statistically significant sex × fatigue interaction with medium effect sizes was found for whole-trial CoP velocity in AP (p = 0.028; η2= 0.17) and ML directions (p = 0.019; η2 = 0.19). Post-hoc test showed that both variables substantially decreased in female participants (p = 0.041-0.045; d = 0.54-0.56), but remained similar in males (p = 0.194-0.294). There were small to medium statistically significant main effects of fatigue on transient index for CoP amplitude in both directions (p = 0.042-0.049; η2 = 0.02-0.14). Notably, CoP AP amplitude increased in the 1st 10-s interval for males (before fatigue: 5.6 ± 1.3 mm; after fatigue: 6.3 ± 1.6 mm), while the CoP AP amplitude in the 3rd interval remained similar after fatigue (before fatigue: 5.5 ± 1.4 mm; after fatigue: 5.1 ± 1.2 mm). In conclusion, the responses to fatigue in terms of postural sway were time interval specific, and there were certain sex-differences in responses to fatigue, which could be related to better ability to adapt balance strategies in females. Moreover, our results demonstrate that the indexes of transient behavior could perhaps detect smaller fatigue-induced changes in postural sway that not seen in whole-trial estimates.